MarineVerse enables more people to sail! - Tizuka, Michelle Mayumi; Dziemidowicz, Greg (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR), 2020)
MarineVerse wants to promote and share the sport of sailing with the world by providing sailing education, growing as a sailor, socializing, and having entertainment using virtual reality technology. Current VR sailing applications are designed for Valve Index, HTC Vive, Oculus Rift, and Oculus Quest, and flagship products are MarineVerse Cup and VR Regatta.